2017
DOI: 10.18805/ijar.b-718
|View full text |Cite
|
Sign up to set email alerts
|

The effects of in ovo pollen extract injection on growth parameters, ileal histomorphology and caecal microflora in fasted broiler chicks

Abstract: This study was carried out to determine the effects of in ovo pollen extract injection on growth parameters, ileal histomorphology, and caecal microflora of fasted broiler chicks. In this experiment, 2×2 factorial experimental design was used. One d old, 120 healthy broiler chicks were allocated to 4 treatment groups and 6 replicates (5 mixed sex chicks allocated each replicates). Treatment groups were: A) Pollen extract injection and 24 h fasting (P24); B) Pollen extract injection and 48 h fasting (P48), C) C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The findings in this study however, shows a slight difference from literature as the highest average daily feed intake was recorded consecutively at 10, 0, 5 and 15% inclusion levels of PSKA, with ash contents being highest at 0% inclusion level (7.59), followed by 15% (6.74), 10% (6.22) and least at 5% (5.44) inclusion level. The variability in feed intake due to ash content could be due to developing and growing nature of the chicks used as their GIT enzymes are still developing due to their young age (Coskun et al 2017). The high ash content in T 1 diet could also be due to bone meal having higher ash than PKSA.Also the low percentage weight for liver and small intestine are probably reflective of lower body weight due to reduced feed intake in these groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in this study however, shows a slight difference from literature as the highest average daily feed intake was recorded consecutively at 10, 0, 5 and 15% inclusion levels of PSKA, with ash contents being highest at 0% inclusion level (7.59), followed by 15% (6.74), 10% (6.22) and least at 5% (5.44) inclusion level. The variability in feed intake due to ash content could be due to developing and growing nature of the chicks used as their GIT enzymes are still developing due to their young age (Coskun et al 2017). The high ash content in T 1 diet could also be due to bone meal having higher ash than PKSA.Also the low percentage weight for liver and small intestine are probably reflective of lower body weight due to reduced feed intake in these groups.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have consistently suggested the importance of the first seven days of broiler chicken's life, its influence on the overall performance of the bird and the need to provide adequate nutritional management at this period (Coskun et al 2017, Mahapatra et al 2017. Wahlström et al (2001) had reported that during the first seven days of a broiler's life, about 80% of its energy requirements is used for growth, while only about 20% is for maintenance; howeverthe bird's intestinal growth represents most of these body weight increases at this stage of development (Mahapatra et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have used ascorbic acid, carbohydrates, amino acids, vitamin-minerals, hormones and bee products (Kocamis et al, 1999;Salmanzadeh et al, 2012;Coşkun et al, 2014a;Coşkun et al, 2014b;Moghaddam et al, 2014;Sgavioli et al, 2015;Yair et al, 2015;Coskun et al, 2017;Maman et al, 2019;Alizadeh et al, 2022) in the in ovo method in recent years. Resveratrol is a polyphenolic phytoalecsin synthesized by plants in response to environmental stress or pytopathogene attacks.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of different levels of PEs or their derivatives on hatching, productive and immune results through IO has been studied by researchers, who examined, for instance, α-galactoside of lupin seeds (Villaluenga et al, 2004), αgalactoside of pea (Pilarski et al, 2005), caffeine (McGruder et al, 2011), grape seed (Hajati et al, 2014), pollens of sunflower (Coşkun et al, 2014), wheat (Tako et al, 2014), garlic, tomato (Fazli et al, 2015), thyme, savory (Saki and Salary, 2015), or Silybum marianum (Morovata et al, 2016). It is worth mentioning that some PEs were tested for their antiviral (Rezatofighi et al, 2014) and antimicrobial activity (Burt, 2004), as natural anticoccidial (Dalloul et al, 2006), as biological antioxidants reacting with free radicals (Wallace et al, 2010), for anti-inflammatory activity of the phytochemicals contained (Sahin et al, 2013) and for immunostimulant functions (Frankic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%